The Tractatus and natural sciences - Tejedor, Chon (Analysis. Journal of Philosophical Research, 2022)
In this article, I examine the conception of the natural sciences that emerges in Wittgenstein’s Tractatus Logico-Philosophicus. I begin, in part 1, by arguing that Wittgenstein’s early philosophy does not express a hostility towards the natural sciences, but towards a scientism that Wittgenstein views as posing a threat not just to philosophy and ethics, but also to scientific practices themselves. In the part 2, I examine Wittgenstein’s critique, in 5.133-5.1362 of the Tractatus, of a philosophical approach to the natural sciences that focuses on the notion of natural necessity, and which Wittgenstein considers to be nonsensical. In part 3, I move to exploring the alternative conception of the natural sciences defended by Wittgenstein in 6.32-6.3611 of the Tractatus, a conception that brings together a deflationary version of scientific realism and pragmatism. Finally, in part 4, I end with a series of observations on the contrast between natural science, traditional metaphysics and scientism, in Wittgenstein’s early philosophy.